Age, an Important Sociodemographic Determinant of Factors Influencing Consumers' Food Choices and Purchasing Habits: An English University Setting - Ogundijo, Daniel A.; Tas, Ayten A.; Onarinde, Bukola A. (Frontiers in Nutrition, 2022)
The purchasing behaviors of university staff (n = 188) and their use of nutrition labels in making food choices were investigated by an online survey. The age of the participants significantly impacted their purchasing behaviors. This effect was not observed with other sociodemographic characteristics studied (level of education, gender, employment status and ethnicity). The impact of age on the extrinsic factors affecting food choice (personal preference, previous knowledge, convenience, religion/beliefs) and intrinsic factors (quantity, country of origin, method of preparation/serving, fat, salt, protein and added sugar contents) were further explored. The use of nutrition labels among different age groups when buying for the first time was significant for breakfast cereals and fruit juices.